Back to the Future or Forward to the Past: Ocean Voyaging and Slow Travel - Christina Gerhardt (Studies in 20th & 21st Century Literature, 2020)
Going back to previous modes of travel, such as walking or sailing, to ensure a future, is currently being engaged by everyone from ambling environmentalists to scientists and technologists. In Germany and in Sweden, scientists are working to develop large cargo sailing ships. These ships of the future hearken back to the past of ocean voyaging. They dovetail with contemporary literary reflections on ocean voyaging and slow travels, such as Judith Schalansky’s Atlas of Remote Islands: Fifty Islands I Have Never Set Foot On and Never Will (2009). Weaving together an analysis of Schalansky’s atlas with environmental humanities discourses on deep time, this article puts forward a model of ocean voyaging as slow travel, thereby expanding the modes of travel that are included in slow travel. Additionally, it considers the place of climate refugee migrations in the concept of slow travel in light of Jenny Erpenbeck's novel Going, Gone, Went (2015).
Keywords: Environmental Humanities; Comparative Literature; German Liteature; Sustainability